NATUREZA DA LINGUAGEM: FACULDADE COGNITIVA OU INTELIGÊNCIA EM EVOLUÇÃO? - Senna, Maria Teresa Telles (Organon, 2003)
The objective of this work is to study the acquisition of languageby proceeding along two extremely fertile paths, that of the GenerativistSchool, with Noam Chomsky at its forefront, and that of the Inter-actionistSchool _cognitivist _also called constructivist, with Jean Piaget as its representative.Occasionally, the term constructivism manifests itself in interpretationsthat are different from the Piaget model for the acquisition oflanguage. This work has no interest in provoking uproar in respect to thesubject. The core of the theoretical foundation is found in the nature of languageunder the two points of view noted above, to be developed in theprocess of their presentation. This article presents, eminently, theoreticaldiscussions and, therefore, forms part of the methodology summarized insome classical texts pertaining to the theme. Our intention is that of contributingthrough supplementary studies directed towards the nature of the acquisitionof the language for questions that are complex and polemic. In thisway, we also hope to supply, to those interested in the subject, data for theexisting bibliography regarding this issue.